Anomalous coronary arteries: what is known and what still remains to be learned?. (January 2020) - Molossi, Silvana; Sachdeva, Shagun
Abstract : Purpose of review: To report what is known and unknown regarding coronary anomalies in children, particularly anomalous aortic origin of a coronary artery, efforts undertaken to answer several questions regarding evaluation and management of this challenging young population, and where the future is heading. Recent findings: Patients with anomalous aortic origin of a coronary artery (AAOCA) present as an incidental finding at least half of the time, advanced imaging is essential to define anatomic characteristics of this lesion, assessment of myocardial perfusion with stress cardiac magnetic resonance imaging is feasible and contributes to risk stratification, certain patient populations require invasive assessment of coronary flow with measurement of fractional flow reserve, and surgical intervention can be safely performed through long-term data on impact to prevent sudden events is lacking. Summary: Optimal risk stratification in AAOCA is yet to be defined, though substantial strides are being made with a standardized approach to the evaluation and management of these patients. Continued collaboration among centers and the scientific community will positively impact patients and families living with AAOCA.